Noticing Acute Changes in Health in Long-Term Care Residents. Issue 2 (16th March 2023) - Bowen, Mary Elizabeth; Rowe, Meredeth; Flynn, Aidan; Basehore, Heather; Shin, Ju Young
Abstract: Purpose: Early signs of acute conditions and increased fall risk often go unrecognized in patients in long-term care facilities. The aim of this study was to examine how healthcare staff identify and act on changes in health status in this patient population. Design: A qualitative study design was used for this study. Methods: Six focus groups across two Department of Veterans Affairs long-term care facilities were conducted with 26 interdisciplinary healthcare staff members. Using thematic content analysis, the team preliminarily coded based on interview questions, reviewed and discussed emerging themes, and agreed on the resultant coding scheme for each category with additional independent scientist review. Results: Themes included describing and explaining how "normal" or expected behavior is identified by staff, noticing changes in a resident, determining the significance of the change, hypothesizing reasons for an observed change, response to an observed change, and resolution of the clinical change. Conclusions: Despite limited training in formal assessment methods, long-term care staff have developed methods to conduct ongoing assessments of the residents. This technique, individual phenotyping, often identifies acute changes; however, the lack of formal methods, language, or tools to communicate the changes means that these assessments are not often formalized in a manner that informs the residents' changing care needs. Clinical Relevance to the Practice of Rehabilitation Nursing: More formal objective measures of health change are needed to assist long-term care staff in expressing and interpreting the subjective phenotype changes into objective, easily communicated health status changes. This is particularly important for acute health changes and impending falls, both of which are associated with acute hospitalization.